ECG Research Using Elements of Matrix Analysis and Phase Planes - Smidtaite, R.; Navickas, Z.; Venskaityte, E. (Elektronika ir Elektrotechnika, 2010)
Electrocardiogram (ECG) is a diagnostic tool that measures activity of the heart. The dynamics of coherence between two different ECG parameters is investigated. Two time series, representing RR and JT parameters, are cointegrated into one time series and then matrix analysis is applied. While studying dynamical systems phase portraits are an invaluable tool. Therefore, to reveal similarities and differences of several characteristics phase portraits are drawned. In this study data of over twenty sportsmen are investigated. The view of phase portraits depends on physical load and training. The coherence of two parameters is to be extended to coherence of three parameters in further studies.